Sightings of Risso’s dolphin (Grampus griseus) off the southern coast of Linosa island (south-central Mediterranean Sea) - CORRIAS, VALENTINA; FILICIOTTO, FRANCESCO; GIARDINA, FABIO (Mediterranean Marine Science, 2021)
The distribution, habitat preferences and site fidelity of Risso’s dolphin in the Strait of Sicily are very little known. During sea surveys conducted in three summer seasons, we sighted this species offshore Linosa Island in groups of variable numbers of individuals (2-20, average 9.7 ± 7.0 SD). Sightings were concentrated in a small area whose medium depth (average, 591 m) and bathymetric features are in line with the known habitat preferences of the species. A total of 32 individuals belonging to four age classes were photo-identified; eight were re-sighted once over the years. We report for the first time the presence of Risso’s dolphin in the waters around Linosa Island. The results seem to indicate a site fidelity over the years.